FETAL OUTCOME IN PRE-EXISTING TYPE 2 DIABETIC MOTHERS - PARAS, .; AKHTAR, T; NAZ, S; NIRGUS, R; ZOYA, .; KAINAT, . (Biological and Clinical Sciences Research Journal, 2024)
Diabetes mellitus is one of the most common medical complications of pregnancy at present. Pre-existing diabetes mellitus is associated with morbidity in the mother and offspring, as well as infant mortality. Objective: To determine the frequency of fetal outcomes in pre-existing type 2 diabetic mothers at Shaikh Zaid Women Hospital. Methods: This Cross-sectional study was conducted at the Department of Obstetrics and Gynecology, The Shaikh Zaid Women Hospital from December 2023 to May 2024. Data were collected through a non-probability consecutive sampling technique. Gynaecologist sonographers performed clinical assessment and transvaginal pelvic ultrasound. Results: Data were collected from 168 patients. Preterm delivery was the most frequent outcome, observed in 60 cases (35.7%), followed by neonatal hypoglycemia in 50 cases (29.8%) and respiratory distress in 35 cases (20.8%). Other notable complications included low birth weight (16.7%), congenital anomalies (11.3%), and macrosomia (10.7%). Neonatal death was reported in 3 cases (1.8%), and a low Apgar score was recorded in 15 cases (8.9%). The mean maternal age was 31.4 ± 4.8 years, with a median age of 31 (IQR: 28–35). The average HbA1c level was 6.8 ± 0.4%, with a median of 6.7% (IQR: 6.5–7.1), indicating generally well-controlled glycemic levels. Conclusion: Pre-existing type 2 diabetes mellitus is associated with a high frequency of adverse fetal outcomes, including preterm delivery, neonatal hypoglycemia, and respiratory distress. Optimal glycemic control and targeted antenatal care are essential to mitigate these risks and improve neonatal outcomes.